KONSEP DAN OPERASIONALISASI PEGADAIAN SYARIAH - Norvadewi, Norvadewi (Mazahib, 2007)
In Islamic jurisprudence, the contract of pawn is called as rahn meaning to deposit something as security for a loan. Rahn initially was used to accomplish the transaction of loan by means of qard. In its development as practiced by Syariah Pawnbroker, another form of contract in rahn has been employed, i.e. mudharabah. When a costumer decided to use mudharabah in the rahn contract, the rahn functions to save up article deposited as for future use. The Syariah Pawnbroker then serves as investor, while the customer serves as businessman.